2010
DOI: 10.1007/bf03393080
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Textual Prompting and Reading Fluency on the Acquisition of Intraverbals

Abstract: The study examined the effects of textual prompt fading on the acquisition of intraverbals in 3 individuals with developmental disabilities. An alternating treatments design was used to assess the two independent variables. The first independent variable was transfer of stimulus control without component skill fluency. The second independent variable was transfer of stimulus control with component skill fluency, in which participants were taught the textual responses used in the scripts to a level of fluency p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 12 publications
(12 reference statements)
3
24
0
Order By: Relevance
“…The results of this review indicate that culture and language backgrounds are rarely reported in the recent behavior-analytic language acquisition literature in the Daly et al (2006) 3 Kurdish N/A Referral for reading problems Hispanic Hispanic Emmick et al (2010) 3 journals we examined. Of the 103 articles that met inclusion criteria for review, nine studies listed cultural backgrounds of their participants (e.g., Ingvarsson and Hollobaugh 2010;Pelaez et al 2011), and only one study (Williams et al 2003) listed the language background of the participants.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The results of this review indicate that culture and language backgrounds are rarely reported in the recent behavior-analytic language acquisition literature in the Daly et al (2006) 3 Kurdish N/A Referral for reading problems Hispanic Hispanic Emmick et al (2010) 3 journals we examined. Of the 103 articles that met inclusion criteria for review, nine studies listed cultural backgrounds of their participants (e.g., Ingvarsson and Hollobaugh 2010;Pelaez et al 2011), and only one study (Williams et al 2003) listed the language background of the participants.…”
Section: Discussionmentioning
confidence: 83%
“…In JABA, six articles (6 %; Charlop-Christy et al 2002;Chaabane et al 2009;Daly et al 2006;Ingvarsson and Hollobaugh 2010;Pelaez et al 2011;Williams et al 2003) included cultural descriptors (e.g., Ethiopian-American, Chinese-American, and Korean-American participants; Charlop-Christy et al 2002), and one article (1 %; Williams et al) included information about language background (e.g., English or Spanish language backgrounds). In TAVB, three articles (3 %; Yi et al 2006;Emmick et al 2010;Ingvarsson and Le 2011) included cultural descriptors (e.g., Iranian-American and Caucasian participants; Yi et al 2006), and we did not find any articles that included information about language background.…”
Section: General Proceduresmentioning
confidence: 81%
See 2 more Smart Citations
“…We identified 40 studies involving intraverbal responses as one of the primary dependent variables. Seven studies focused on evaluating the effectiveness of various prompt strategies, including textual prompts (e.g., Emmick, Cihon, & Eshleman, 2010;Finkel & Williams, 2001;Vedora, Meunier, & Mackay, 2009), echoic prompts (e.g., Ingvarsson & Hollobaugh, 2011;Ingvarsson & Le, 2011), and tact prompts (e.g., Goldsmith et al, 2007;Kodak, Fuchtman, & Paden, 2012a) during intraverbal training.…”
Section: Intraverbalsmentioning
confidence: 99%